Adult stature estimation from radiographically determined metatarsal length in Egyptian population. (December 2017) - Ibrahim, Mahrous A.; Elelemi, Azza H.; Ibrahim, Mostafa S.; Bandy, Altaf H.
Abstract: Background: Estimation of the stature might be critical in the identification of skeletal remains. Usually, the small bones found among human remains are not only the most numerous, but also the best-preserved parts. Objective: The primary aim of this work is to determine whether metatarsals can be used for the estimation of adult stature in an Egyptian population using radiologically determined metatarsal lengths and to propose regression equations and test the formulae for determining adult stature. Subjects and methods: The 1st and 2nd metatarsals of the left foot of the 220 healthy adult participants were assessed by plain X-ray in a dorso-plantar position utilizing a digital radiography machine commonly used in hospitals. The measurements were obtained by default program on console of the machine that offers manipulation and measurements on the obtained images. Results: The study clearly illustrated that the 1st metatarsal maximum length (M1) in males was the most noteworthy correlation with the true stature. The derived regression equation is as per the following: S = 851.52 + 12.26 M1, R = 0.8904 M1. Our findings in the current study were more accurate when comparing our study statistical findings with the results of other population groups. Conclusion: the regression equations for stature estimation obtained in our study may be utilized for the identification of stature of skeletons among adult Egyptians from medicolegal point of view.